KETERPAHAMAN BACAAN SISWA KELAS VI SD NEGERI NUSA TUNGGAL - F.Pika Suhendra (Universitas Katolik Musi Charitas, 2021)
The background of this research is to know the ability of narrative writing in the elementary school in Jayamulya village, Semendawai sub-district, tribe III, East Oku district. The purpose of this study was to determine the ability to write narrative texts for fifth grade students in Jayamulya Village, Semendawai District, III OKU Timur. This research is a qualitative research, namely research that has a naturalbackground, is descriptive, further improves the process, tends to analyze data, and focuses on meaning. The method of datacollection was carried out by means of a population andsamples taken from two elementary schools in JayamulyaVillage and obtained 21 students, it is known that of the 21 students studied they were less able to write narratives. From the results of the research and discussion, it can be concluded that all fifth grade students in Jayamulya Village are less able towrite narratives with the theme Aktivitas di Rumah Selama Pandemi Corona